The Impact of Covid-19 on the Level of Productivity and Industrial Development in South Africa - Thakaramahlaha Lehohla; Pule Kholopane (The Thinker)
South Africa has identified the manufacturing sector as a key driver of the economy via the re-industrialisation drive, with incentive programmes such as the Manufacturing Competitive Enhancement Programme (MCEP), Cluster Development Programme (CDP), 12I Tax Allowance Incentive, and Special Economic Zones (SEZs).